Hollow Structural Sections in Flexure - Prasad, Janardan (My University, 1972)
A research programme is presented for assessing the capability of Hollow Structural Sections for design in flexure. This investigation is the continuation of earlier work on the topic which provided guidelines primarily for rectangular sections with relatively low flange slenderness. The present work attempts to relate the tube slenderness and yield strength to the rotation capacity and moment resistance of round sections subjected to bending moment. Also an attempt is made to establish similar guidelines for rectangular sections with relatively high flange slenderness.
An experimental programme on 16 different sections was performed to evaluate the moment-curvature relationship which is of fundamental importance in flexural design. The occurrence of local buckling in compression flange and the consequent reduction in moment resistance is the critical factor which separates the sections into the categories governed by allowable stress or plastic method of design.
An attempt is made to develop an analytical method to determine the critical buckling stress for round sections subjected to pure moment in the inelastic range.
The experimental results are compared with the analytical predictions. Finally a design criterion to separate the sections into the design categories is established.
Title: Hollow Structural Sections in Flexure, Author: Janardan Prasad, Location: Thode